2020
DOI: 10.3892/etm.2020.9371
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sphingomyelin synthase 2 reduces cerebral ischemia/reperfusion injury by inhibiting microglial inflammation in mice

Abstract: Recanalization of blood flow after ischemia can lead to ischemia/reperfusion injury, and inflammation plays an important role in the mechanisms behind cerebral ischemia/reperfusion injury. Sphingomyelin synthase 2 (SMS2) deficiency reduces inflammation; however, the effect and mechanism of action of SMS2 on the inflammatory response after cerebral ischemia/reperfusion injury are still unclear. Wild-type (WT) and SMS2 knockout C57BL/6 mice were used to establish a model of cerebral ischemia/reperfusion. The neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Recently, it was shown that the lack of SMS2 also suppressed the activation of microglia through the inhibition of NF-κB and reduced ischemic injury. ( Yang et al, 2020 ).…”
Section: Stroke and Ceramide Metabolismmentioning
confidence: 99%
“…Recently, it was shown that the lack of SMS2 also suppressed the activation of microglia through the inhibition of NF-κB and reduced ischemic injury. ( Yang et al, 2020 ).…”
Section: Stroke and Ceramide Metabolismmentioning
confidence: 99%
“…Sphingomyelins are also involved in signal transduction pathways and in the regulation of cholesterol and protein trafficking to myelin (Poitelon, Kopec, & Belin, 2020). In addition to their role in myelin architecture, sphingomyelins are involved in microglial activation and inflammation (Fitzner et al, 2020; Yang, Hu, Yang, & Meng, 2020). Chronic stroke infarcts were enriched in sphingomyelins 7 weeks after stroke (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38 NF-κB is a key molecule in the TLR4 signaling pathway, which regulates the expression of pro-inflammatory cytokines and induces inflammatory damage. 39 CUR is regarded as an activator of Nrf2, which plays an important role in inhibiting LPS-induced NF-κB activation and microglial activation caused by LPS. 40 Reportedly, the NLRP3 inflammasome is involved in the NF-κB-mediated inflammatory response in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, a membrane receptor, is responsible for LPS recognition and signal initiation 38 . NF‐κB is a key molecule in the TLR4 signaling pathway, which regulates the expression of pro‐inflammatory cytokines and induces inflammatory damage 39 . CUR is regarded as an activator of Nrf2, which plays an important role in inhibiting LPS‐induced NF‐κB activation and microglial activation caused by LPS 40 .…”
Section: Discussionmentioning
confidence: 99%